1988
DOI: 10.1159/000167662
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy and Polycystic Kidney Disease

Abstract: We report a patient with polycystic kidney disease, advanced renal failure, and nephrotic-range proteinuria. Kidney biopsy revealed IgA nephropathy with lesions of focal and segmental glomerular sclerosis. This association had not been previously described and is probably coincidental. This case supports the assumption that the nephrotic-range proteinuria observed in some polycystic patients could be the consequence of another superimposed glomerular disease. This glomerulopathy can worsen the course of azotem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Murphy et al [5] described a 44-year-old man with ADPKD who presented with the nephrotic syndrome and a marked deterioration in renal function, and was found to have focal glomerulosclerosis on open renal biopsy. Other authors have described ADPKD in conjunction with IgA nephrop athy [6], and idiopathic crescentic, rapidly progressive glo merulonephritis [7,8]. All of these cases demonstrated ei ther advanced renal failure or an accompanying increase in the rate of decline in renal function.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Murphy et al [5] described a 44-year-old man with ADPKD who presented with the nephrotic syndrome and a marked deterioration in renal function, and was found to have focal glomerulosclerosis on open renal biopsy. Other authors have described ADPKD in conjunction with IgA nephrop athy [6], and idiopathic crescentic, rapidly progressive glo merulonephritis [7,8]. All of these cases demonstrated ei ther advanced renal failure or an accompanying increase in the rate of decline in renal function.…”
Section: Discussionmentioning
confidence: 97%
“…More significant proteinuria and the nephrotic syndrome are well recognised [1,4], but have usually been attributed to the polycystic kidney dis ease and in only a few cases investigated further [5][6][7][8]. Murphy et al [5] described a 44-year-old man with ADPKD who presented with the nephrotic syndrome and a marked deterioration in renal function, and was found to have focal glomerulosclerosis on open renal biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Licina et al [5] described a case of APKD with nephrotic proteinuria and acute renal failure; renal biopsy showed crescentic glomerulonephritis. Panisello et al [4] described another case in which renal biopsy demonstrated IgA nephropathy with FGS lesions. In these 2 cases, the development of nephrotic proteinuria appeared to be the consequence of a superimposed glomerular disease.…”
Section: Discussionmentioning
confidence: 98%
“…A few APKD patients in which proteinuria reached nephrotic range have been described [2][3][4][5][6] and the scarce histologic descriptions have shown several glomerular abnormalities (IgA nephropathy, rapidly progressive glomerulonephritis, focal glomerulosclerosis) [4][5][6]. On the other hand, a consid erable interest concerning the implications of adaptive hemodynamic and hypertrophic factors in the progression of renal insufficiency in APKD has risen in the last years Accepted: August 2.1991 [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…I n fact, APK D is never listed as a cause of nephrotic syndrome (NS) and neither is it described as a complication of this genetic disease [I], In those rare patients who develop this complication, several histologic diagnoses have been seen. These include IgA nephropathy, rapidly progressive glomerulo nephritis, focal glomerulosclerosis in rare cases and membranous glomerulonephritis (MGN) [2][3][4], We report here a case of APKD with NS where the kidney biopsy showed MGN.…”
Section: Membranous Glomerulonephritis Associated With Autosomal Domimentioning
confidence: 99%